Introduction - Szulakiewicz, Władysława; Topij-Stempińska, Beata (Studia Paedagogica Ignatiana, 2021)
Care is an integral part of human life. First, parents take care of their children by supporting their development, education and upbringing. They try to raise their children in the best conditions possible. As time goes by, the roles are reversed and it is the child who takes care about his or her elder parents. Sometimes, if parents are unable to provide their children with proper care, various institutions or organizations take this role. These institutions attempt to protect, educate and bring up such children in the best possible manner. And, by analogy, if adult children are not able to care about their elder parents, they ask proper institutions to protect and support them. Pedagogues, who were interested in studying the issue of care, dealt both with theory and promotion of good educational practices. That is why, the collection of works concerning care includes both theoretical ones, which explain, g. w. the term “care”, its scope, functions and tasks, and works that describe the activities of people or institutions which deal with care.